Knowledge Level of Human Papillomavirus, Cervical Cancer and Vaccination Status among Mothers with Daughters in High School - Myung Sook Yoo (Korean Society of Women Health Nursing, 2014)
PURPOSE: The goal of this study was to examine knowledge level of human papillomavirus (HPV), cervical cancer, and vaccination status among Korean mothers' with a daughter in high school. METHODS: A cross-sectional descriptive study was conducted with a convenience sample of 234 Korean mothers. RESULTS: The mean score of HPV knowledge level was 4.21 out of 20, and cervical cancer knowledge was 3.88 out of 7. There were low levels of daughters' who received HPV vaccination (3.8%) and high levels of mothers' intention to get their daughters' vaccinated with HPV (85.0%). The major barrier to HPV vaccination was the concern for side effect from the vaccination. The most effective recommendation for HPV vaccination came from health care providers. CONCLUSION: HPV educational programs targeting mothers of daughters in high school is needed. Future studies need to determine actual HPV vaccination rates and factors related to high uptake using a larger sample from various socioeconomic background.